Enhancement of dalesconols A and B production via upregulation of laccase activity by medium optimization and inducer supplementation in submerged fermentation of Daldinia eschscholzii. (September 2015) - Pan, Zheng-Hua; Jiao, Rui-Hua; Lu, Yan-Hua; Tan, Ren-Xiang
Highlights: Effects of medium components on DA and DB production were investigated. Laccase appeared to be a key enzyme for DA and DB production in D. eschscholzii . Carbon and nitrogen sources were optimized by RSM for submerged fermentation. Induction of laccase activity by inducer further enhanced DA and DB production. Scale-up experiments had been achieved in a stirred bioreactor. Abstract: Dalesconols (dalesconols A and B) are novel polyketides with strong immunosuppressive activity produced by Daldinia eschscholzii . In this work, the effects of different media (M1, M2, and M3) on fungus growth and dalesconols biosynthesis were firstly tested and compared. Intermediates and enzyme analysis indicated that laccase had the major contribution to dalesconols biosynthesis. The key role of laccase on dalesconols biosynthesis was further experimentally confirmed, which suggested that the modified M2 was more favored for laccase and dalesconols production. Thereafter, the medium composition was optimized by RSM with a fermentation titer of 36.66 mg/L obtained. Furthermore, Ca 2+ induction was employed to up-regulate of laccase activity and further enhanced dalesconols production (76.90 mg/L), which was 308% higher than that in M2. In addition, dalesconols production reached 63.42 mg/L in scale-up experiments. This work indicated great potential of laccase as a key enzyme on regulation of dalesconols production.